2012
DOI: 10.1143/jpsj.81.054001
|View full text |Cite
|
Sign up to set email alerts
|

On the Classification of Fifth Order Quasi-linear Non-constant Separant Scalar Evolution Equations of the KdV-Type

Abstract: Fifth order, quasi-linear, non-constant separant evolution equations are of the form u t = A ∂ 5 u ∂x 5 +B, where A andB are functions of x, t, u and of the derivatives of u with respect to x up to order 4. We use the existence of a "formal symmetry", hence the existence of "canonical conservation laws" ρ (i) , i = −1, . . . , 5 as an integrability test. We define an evolution equation to be of the KdV-Type, if all odd numbered canonical conserved densities are nontrivial. We prove that fifth order, quasi-line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 10 publications
2
8
0
Order By: Relevance
“…We give explicit formulas for order m = 7, 9 and give the formulas for order m = 11, 13, 15 in a closed form with the explicit form of the coefficients B 0 . We observed that, at all orders, a satisfies the same equations given in (10) The occurrence of the same form for the separant a suggests strongly that these equations belong to a hierarchy. The same form of a has occurred in the classification of fifth order equation [10], where it has been noted that these equations would be intrinsically related to the class of fully nonlinear third order equations [1],…”
Section: Classification Of Scalar Evolution Equations Of Order M = 11supporting
confidence: 52%
See 1 more Smart Citation
“…We give explicit formulas for order m = 7, 9 and give the formulas for order m = 11, 13, 15 in a closed form with the explicit form of the coefficients B 0 . We observed that, at all orders, a satisfies the same equations given in (10) The occurrence of the same form for the separant a suggests strongly that these equations belong to a hierarchy. The same form of a has occurred in the classification of fifth order equation [10], where it has been noted that these equations would be intrinsically related to the class of fully nonlinear third order equations [1],…”
Section: Classification Of Scalar Evolution Equations Of Order M = 11supporting
confidence: 52%
“…The classification of 5th order, constant separant evolution equations is given in [3]. The non-constant separant case is studied by the MSS method in [10] where "KdV-like" equations are defined to be the ones that admit an unbroken sequence of conserved densities at all orders. Although the classification is not complete, it has been shown that the non-constant separant KdV-type equations are of the form u t = a 5 u 5 + Bu 2 4 + Cu 4 + G, where B, C and G are polynomial in a and u 3 and a new exact solution is given [10].…”
Section: Introductionmentioning
confidence: 99%
“…This form can also be obtained from the triviality of ρ (3) , whose explicit expression is given in [11]. This expression involves…”
Section: Resultsmentioning
confidence: 99%
“…We aimed to obtain a similar uniqueness result for general, non-polynomial integrable equations and we applied the method of formal symmetries, based on the existence of "canonical densities" [7], to the classification of integrable evolution equations in 1 + 1 dimensions, u t = F [u] [1,8,11,9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation